Pelatihan Pembuatan Password Yang Kuat, Pengenalan Bahaya Phishing Dan Prinsip Perlindungan Data Pribadi - Ahmad Yani Noor; azis wahyudi; Anas Rahmad Hidayat (Jurnal Pengabdian Masyarakat Permata Indonesia, 2026)
The increased use of digital services in higher education and healthcare facilities is accompanied by a growing risk of cybersecurity incidents, particularly phishing attacks and personal data leaks. Evidence from multiple incidents suggests that human factors remain a major vulnerability; therefore, digital security literacy should be strengthened through measurable educational interventions. This community service program aimed to improve participants’ knowledge and awareness of (1) phishing characteristics and tactics, (2) strong password practices and password hygiene, and (3) personal data protection principles, especially for health data. The online training was conducted via Zoom on March 14, 2026 (3 hours) with 47 participants (students, lecturers, and practitioners) from RSKIA Sadewa, RS DKT Dr. Soetarto, and RSUD Saras Adhyatma Bantul. The program used interactive lectures, case-based simulations, discussion, and pre–post evaluation using Google Forms. Results showed increased correct responses for phishing type recognition (32% to 88%) and phishing message/email identification (28% to 85%). Understanding of personal data protection principles improved (45% to 80%), as did the ability to apply basic digital security practices (41% to 89%). The program effectively improved cybersecurity literacy across participant groups and is feasible to replicate to mitigate risks of data leakage and account compromise in academic and healthcare contexts.